New Grading System for Limbal Dermoid: A Retrospective Analysis of 261 Cases Over a 10-Year Period. Issue 1 (January 2018) - Zhong, Jing; Deng, Yuqing; Zhang, Ping; Li, Saiqun; Huang, Haixiang; Wang, Bowen; Zhang, Henan; Peng, Lulu; Yang, Ruhui; Xu, Jiangang; Yuan, Jin
Abstract : Purpose: To establish a new scoring system for limbal dermoid, in order to unify the diagnostic criteria and assess the prognosis. Methods: A retrospective study was conducted on 261 patients with limbal dermoid. The basic information, clinical features, and pathology of dermoids were recorded, and the prognosis at 1 year after keratoplasty was assessed at follow-up. A new visual scoring system was created for the area of corneal involvement, the area of conjunctival involvement, and the surface shape. Results: There were 154 females and 107 males with mean age of 4 ± 3 years at surgery. After scoring, 59% (136) of patients were classified as grade I, 26% (60) as grade II, and 14% (33) as grade III. The pathological results were 124 dermoid cases, 76 lipodermoid, 5 complex choristoma, and 10 epibulbar osseous choristoma. Moreover, patients with lower clinical scores presented a better prognosis; the mean logarithm of the minimum angle of resolution (logMAR) best-corrected visual acuity in grade I patients was 0.38 ± 0.05, which was better than the grade II value of 0.61 ± 0.09 ( P < 0.05) and the grade III value of 0.94 ± 0.11 ( P < 0.001). Conclusions: New grading systems for limbal dermoid were useful for clinical diagnosis and may have prognostic value in predicting visual acuity. A lower-grade dermoid exhibited better vision postoperatively.